The Spread of Descriptive Geometry in Great Britain Between the XVIII and XIX Century (diségno, 2018)
Between the Eighteenth and Nineteenth Centuries the diffusion of the Monge’s Descriptive Geometry in Europe determines, with different times and outcomes in the various countries, a radical change in the field of representation. It modifies not only the approach to design but also, and substantially, professional education. In Britain, however, the new science, for both political and cultural reasons, officially arrives very late.Its circulation among professionals, craftsmen and designers, though well attested before, sees it grafted onto a series of independent research experiences, also fueling the attempts by British theoreticians to define a universal system of graphic communication.The present study, through a research review on the history of representation related to this era, and the collection of documentary sources, intends to offer a systematic reconstruction of the diffusion of Descriptive Geometry in Great Britain, contextualizing it in the socio-political climate of the time and intertwining new instances of the Monge’s method with the original research conducted across the Channel in those years.
Keywords: Geometrical Drawing; England; porjections; Monge; Nicholson